Morphological Effects in Visual Word Recognition: Children, Adolescents, and Adults - Dawson, Nicola (J Exp Psychol Learn Mem Cogn, 2017)
The process by which morphologically complex words are recognized and stored is a matter of ongoing debate. A large body of evidence indicates that complex words are automatically decomposed during visual word recognition in adult readers. Research with developing readers is limited and findings are mixed. This study aimed to investigate morphological decomposition in visual word recognition using cross-sectional data. Participants (33 adults, 36 older adolescents [16 to 17 years], 37 younger adolescents [12 to 13 years], and 50 children [7 to 9 years]) completed a timed lexical-decision task comprising 120 items (60 nonwords and 60 real word fillers). Half the nonwords contained a real stem combined with a real suffix (pseudomorphemic nonwords, e.g., earist); the other half used the same stems combined with a nonmorphological ending (control nonwords, e.g., earilt). All age groups were less accurate in rejecting pseudomorphemic nonwords than control nonwords. Adults and older adolescents were also slower to reject pseudomorphemic nonwords compared with control nonwords, but this effect did not emerge for the younger age groups. These findings demonstrate that, like adults, children and adolescents are sensitive to morphological structure in online visual word processing, but that some important changes occur over the course of adolescence.